The Influence of Work Discipline and Work Motivation on Employee Performance at The Agency for Personnel and Human Resource Development (BKPSDM) of Malang City - Ludovikus Budiman; Cakti Indra Gunawan; Moh. Askiyanto (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study was to determine the effect of work discipline and work motivation on employee performance at the Malang City Human Resources Development and Personnel Agency (BKPSDM), both partially and simultaneously. This study used a quantitative method. The population consisted of all 44 employees at the BKPSDM office in Malang City. The sampling technique used total sampling. The instrument used a questionnaire. Data analysis in this study used multiple linear regression analysis. Hypothesis testing was conducted using the t-test (partial) and the F-test (simultaneous). The results of the multiple linear regression showed that both independent variables had positive regression coefficient values. In addition, the R Square (R²) value obtained was 0.768, indicating that the contribution of the independent variables to the dependent variable was 76.8%. The results of the partial hypothesis test (t-test) show that both independent variables have a t-value greater than the t-table value, with a significance level of less than 0.05. Meanwhile, the results of the simultaneous hypothesis test (F-test) also indicate that the F-value is greater than the F-table value, with a significance level below 0.05. Therefore, it can be concluded that work discipline and work motivation have a significant effect on employee performance at the Malang City Human Resources Development and Personnel Agency (BKPSDM), both partially and simultaneously. The leadership of BKPSDM Malang City is advised to integrate policies to improve discipline and motivation simultaneously, so that both aspects can complement each other in improving the quality of employee performance in a sustainable manner.